2021
DOI: 10.1098/rspb.2021.0592
|View full text |Cite
|
Sign up to set email alerts
|

A bird's-eye view on turbulence: seabird foraging associations with evolving surface flow features

Abstract: Understanding physical mechanisms underlying seabird foraging is fundamental to predict responses to coastal change. For instance, turbulence in the water arising from natural or anthropogenic structures can affect foraging opportunities in tidal seas. Yet, identifying ecologically important localized turbulence features (e.g. upwellings approximately 10–100 m) is limited by observational scale, and this knowledge gap is magnified in volatile predators. Here, using a drone-based approach, we present the tracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…HF radar) to provide insight at scales that were previously difficult to measure. Although other remote-sensing platforms—such as unoccupied aerial vehicles—can capture both behaviour and the environment at fine-spatial scales [ 100 ], we show that the combination of biologging and HF radar can provide a broader scope of high-resolution behavioural detail and synoptic oceanographic coverage. These results provide further evidence that fine- and intermediate-scale processes are important to pelagic predators and suggest that predator behaviour could help identify gradients in habitat quality (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…HF radar) to provide insight at scales that were previously difficult to measure. Although other remote-sensing platforms—such as unoccupied aerial vehicles—can capture both behaviour and the environment at fine-spatial scales [ 100 ], we show that the combination of biologging and HF radar can provide a broader scope of high-resolution behavioural detail and synoptic oceanographic coverage. These results provide further evidence that fine- and intermediate-scale processes are important to pelagic predators and suggest that predator behaviour could help identify gradients in habitat quality (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…For marine mammals, where much more funding has been available for studies, it appears the noise of tidal turbines does have an effect on seals such that they will avoid areas where they can hear the turbine noise [14], [15]. However some studies have shown that seabird species are attracted to turbines even during operations due to the predictable wake that is created and may be bringing prey species to the surface, making them easier to catch [16], [17]. At established windfarms it has been clearly shown that seals will change their normal foraging areas as they find the foundations preferable places for foraging [18] which may be associated with the 'reef effect' of man-made structures providing new habitat.…”
Section: B Displacementmentioning
confidence: 99%
“…The design, size and location of arrays can have very significant ecological effects of displacement as discussed above; large offshore windfarm arrays may essentially block the movement of highly mobile animals such as seabirds, and large tidal arrays could block marine mammals and large fishes (basking sharks) from using daily routes to foraging areas and/or annual migration routes. For tidal arrays in particular the 'downstream' changes from both the introduction of structures and extraction of energy have significant impacts on the locations of shear, turbulence structures such as kolk boils [33] upwelling [16], [17]. Very large extractions of tidal energy (> 6 GW) have been shown to have further 'downstream' effects on stratification and mixing [27] with effects of up to 10% changes in physical and biological variables over hundreds of km of distance from the site of extraction [34].…”
Section: B Array Design and Locationmentioning
confidence: 99%
“…This scenario can be taken as representative of high-energy conditions such as: fast-flowing tidal currents of ~1 m/s on the continental shelf [3,4]; tidal flow through straits and inlets [5], and around headlands and islands [2]; and tidal flow over a sill [6,7]. Strong currents and associated turbulence can impact physical structures [8] and be of ecological significance [9], and in some cases can pose a challenge to making in-situ measurements.…”
Section: Introductionmentioning
confidence: 99%